Green benefits on educational buildings according to the LEED certification - Kim, Ji-Myong; Son, Kiyoung; Son, Seunghyun (International Journal of Strategic Property Management, 2020)
Countries around the world are making efforts to develop and introduce green building certification systems to save energy and reduce greenhouse gas emissions. As a result of these efforts, green certification systems are rapidly spreading. Consistent with this, certification systems are also being developed and research related to various technologies and regulations is ongoing. However, most research focuses on residential and commercial buildings and there is still a lack of scientific research on educational facilities. To fill the gap and support the former studies, this research statistically studies the economic effects of green certification systems on educational facilities. For this purpose, the benefits, i.g., building price and maintenance & repair costs, were examined for universities in Canada that were admitted to the Canadian Educational Institution. As shown by the results of this study, Leadership in Energy and Environmental Design (LEED)-certified buildings cost 49.9% more to build and had 25.6% lower maintenance and repair costs than non-LEED certified buildings.